Behaviour of Carbon Black Nano-Engineered Cementitious Composite at Elevated Temperature - Kumar, Nitish (My University, 2023)
Nanomaterials have introduced fundamental changes in cement-based composites at sub-microscale and microscale levels, resulting in modifications in molecular structures. These nanoscale alterations significantly influence the macroscale properties of the composites. Nanotechnology's distinctive attributes, such as substantial surface area and enhanced hydration rate, have led to remarkable mechanical strength and durability enhancements. Carbon black, a fine particle of elemental carbon, is known for its high conductivity, UV resistance, and pigmenting abilities. It finds various applications in industries, including rubber, where it reinforces tires and rubber products for improved strength and wear resistance. Including carbon black nanoparticles in cementitious composites has gained attention for its positive impact on mechanical properties. Carbon black's high surface area-to-volume ratio allows enhanced reactivity and filling of pores and microcracks in the cement matrix, leading to improved densification and hydration processes. This research investigates the effects of increased temperature on key properties of nanoengineered composite mortar, focusing on compressive strength, flexural strength, mass loss, and colour change. Results demonstrate that carbon black nanoparticles effectively replace cement in nanoengineered composite mortar, showing favourable properties in fresh and hardened states. The observed strength reduction due to temperature variations is effectively mitigated by incorporating 2% carbon black. Microstructural analysis reveals alterations resulting from carbon black substitution and temperature effects. These findings highlight the potential of utilizing carbon black nanoparticles as a cement alternative in the construction industry, leading to improved nanoengineered composite mortar with enhanced fire resistance properties. This research demonstrates nanomaterials' potential to enhance cement-based composites, improving performance in diverse temperature conditions. It highlights nanotechnology's significant role in advancing construction materials, promising more durable and resilient cementitious composites, revolutionizing the industry.
Keywords: Carbon Black; Elevated Temperature; Mortar; Nanoengineered composites; Slump Flow